2020
DOI: 10.1111/jcmm.16021
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell multi‐omics analysis presents the landscape of peripheral blood T‐cell subsets in human chronic prostatitis/chronic pelvic pain syndrome

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Numerous studies have identified that variations in many inflammatory‐related factors (such as IL‐1β, IFN‐γ, IL‐17, etc.) could be detected in the peripheral blood serum samples of CP/CPPS patients as well as rodent EAP models 33,34 . Here, we found that HA is more highly expressed in serum samples derived from CP patients than in those derived from healthy controls, as detected by ELISA, and is positively associated with increased pain, urination symptoms, and quality of life scores on the NIH‐CPSI questionnaire.…”
Section: Discussionmentioning
confidence: 65%
“…Numerous studies have identified that variations in many inflammatory‐related factors (such as IL‐1β, IFN‐γ, IL‐17, etc.) could be detected in the peripheral blood serum samples of CP/CPPS patients as well as rodent EAP models 33,34 . Here, we found that HA is more highly expressed in serum samples derived from CP patients than in those derived from healthy controls, as detected by ELISA, and is positively associated with increased pain, urination symptoms, and quality of life scores on the NIH‐CPSI questionnaire.…”
Section: Discussionmentioning
confidence: 65%
“…ese fourteen OTUs explain the difference in the microbiota of prostatitis-like symptoms and fertile men: Burkholderiaceae, Achromobacter, Aerococcus, Blautia, Burkholderiales, Propionibacterium, Betaproteobacteria, Haemophilus, Burkholderia, Massilia, Rhizobiaceae, and Neorhizobium. In general, they are little-known microorganisms in the clinical Advances in Urology field, so sequencing is a powerful tool that allows us to discover the world surrounding enigmatic infectious diseases such as prostatitis [26][27][28]. Culture-based studies detected fewer anaerobic bacteria than NGS [10].…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 , 29 , 30 ]. Based on the important effects of IFN- γ in EAP and CP/CPPS [ 9 11 ], we determined the effects of genetic polymorphisms of IFNG and IFNGR1 in CP/CPPS. Initially, functional annotation of the 8 genotyped SNPs of IFNG and IFNGR1 was performed by GTEx database, RegulomeDB, and HaploReg tools, which indicated that these 8 SNPs might have regulatory effects in human whole blood.…”
Section: Discussionmentioning
confidence: 99%
“…[12,29,30]. Based on the important effects of IFN-γ in EAP and CP/CPPS [9][10][11], we determined the effects of genetic polymorphisms of IFNG The results of codominant and log-additive models showed that rs2069718 in IFNG was correlated with the elevated CP/CPPS risk, and rs10457655 in IFNGR1 was correlated with increased NIH-CPSI score. Combined with the autoimmune characteristics of CP/CPPS and the roles of rs2069718 and rs10457655 in inflammatory diseases [30][31][32], we speculated that rs2069718 and rs10457655 might be involved in the pathogenesis of CP/CPPS through other mechanisms as predicted by the HaploReg tool [20], including protein 7 Disease Markers binding and regulatory motif alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation